Reinterpretasi Pengembangan Koleksi (Analisis Wacana Kritis The Storied Life Of A.J. Fikry) - Putri, Ina Kencana (Jurnal Tadwin, 2022)
This research disscus about reinterpretation collection development at a small bookstore on the novel that tittled ‘The Storied Life of A.J. Fikry’. This research aim to alaliyze how reinterpretation in a collection development at bookstore using mimetic approach and critical discourse analysis. This novel represent back and forth plot in some chapter, but the hop of time form right now and past are not really explained. From the research was obtenied some social aspect one of them was the character of A.J. Fikry, which he was potraited as a grumpy person, arrogant and a bit weird. Whe the location of the bookstore is on the Alice Island which the measure of the island is only 55m2. In the collection development, obtained result that the collection develompent start from salesperson that offering discount and new titeled book toward bookstore. Other than that, the problem in the bookstore is influenced by personal emotion, other than that the emersion of readaing club was helped bookstore to apart the problem of the collection development.